2019
DOI: 10.1016/j.bjorl.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic central neck dissection and local recurrence in papillary thyroid microcarcinoma: a meta-analysis

Abstract: For patients with papillary thyroid microcarcinoma, thyroidectomy plus prophylactic central neck dissection is a safe and efficient procedure and it results in lower recurrence rate. Since the evidences are of low quality (non-randomized studies), further randomized trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 29 publications
2
42
1
Order By: Relevance
“…The most frequently reported surgeryrelated aftermaths included hypoparathyroidism, hypocalcemia, and recurrent laryngeal nerve injury. [9][10][11][12] To date, it remains unclearly determined if TT plus pCND offers greater oncological benefits without concurrently heightening the risk of postsurgical adverse events among cN0 PTC patients. 6 Indeed, potential reasons for this controversy of pCND include meta-analysis evidence derived largely from low-quality retrospective-based studies, [9][10][11][12] recommendations merely grounded on expert opinions, 5 and lack of adequate randomized and prospective controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported surgeryrelated aftermaths included hypoparathyroidism, hypocalcemia, and recurrent laryngeal nerve injury. [9][10][11][12] To date, it remains unclearly determined if TT plus pCND offers greater oncological benefits without concurrently heightening the risk of postsurgical adverse events among cN0 PTC patients. 6 Indeed, potential reasons for this controversy of pCND include meta-analysis evidence derived largely from low-quality retrospective-based studies, [9][10][11][12] recommendations merely grounded on expert opinions, 5 and lack of adequate randomized and prospective controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, performing a prophylactic central dissection in a center with a large flow of patients, in selected cases such as those studied in our series, is not associated with an increased risk of complications. Several recent meta-analyses underline how it is associated with a lower number of local relapses [ 63 , 64 ]. However, this position remains contested; some authors report the importance of different approaches, such as radioactive iodine ablation, in low-risk cases and cite insufficient evidence for routinely performing central neck dissection to improve patients’ prognosis [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large meta-analysis of over 1200 patients, Zetoune et al reported benefit of neither loco-regional control nor overall survival with a prophylactic central neck dissection in patients with PTC [53]. Up-to-date, there are several systematic reviews with contradictory results on the role of prophylactic CND due to differences in inclusion criteria, size of the tumor, and heterogeneity in the interventions [50,[54][55][56][57][58][59]. As there is a lack of evidence to support any benefit from prophylactic central neck dissection in low-risk patient groups, the concept of aggressive neck surgery to upstage and facilitate RAI seems illogical.…”
Section: Opponents Of Prophylactic/elective Cndmentioning
confidence: 99%